Scale model on performance prediction in recreational and Elite Endurance Runners - Tartaruga, M. P.; Mota, C. B.; Peyré-Tartaruga, L. A.; Brisswalter, J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To identify the effect of allometric scaling on the relationship between running efficiency (REff) and middle-distancerunning performance according to performance level. Methods: Thirteen male recreational middle-distance runners (mean ± SD age 33.3 ± 8.4 y, body mass 76.4 ± 8.6 kg, maximal oxygen uptake [VO2max] 52.8 ± 4.6 mL/kg·min; G1) and 13 male high-level middle-distance runners (age 25.5 ± 4.2 y, body mass 62.8 ± 2.7 kg, VO2max 70.4 ± 1.9 mL/kg·min; G2) performed a continuous incremental test to volitional exhaustion to determine VO2max and a 6-min submaximal running test at 70% of VO2max to assess REff. Results: Significant correlation between REff and performance were found for both groups; however, the strongest correlations were observed in recreational runners, especially when using the allometric exponent (respectively for G1, nonallometric vs allometric scaling: r = .80 vs r = .86; and for G2, nonallometric vs allometric scaling: r = .55 vs r = .50). Conclusion: These results indicate that an allometric normalization may improve endurance-performance prediction from REff values in recreational, but not in elite, runners.